Women's experience of sexuality after radical cystectomy – a qualitative study. (2nd November 2023) - Löfgren, Annica; Stenzelius, Karin; Liedberg, Fredrik; Wangel, Anne-Marie
Abstract: Purpose: The aim of this study was to explore how women experienced sexuality after radical cystectomy due to bladder cancer. Methods: We performed an interview study with qualitative design with content analysis. Inclusion criteria were age below 75 years. In total 10 women, with a median age of 64 years at surgery, were interviewed at median 24 months post radical cystectomy. Results: The 10 women described sexual life as affected after surgery but they all tried to find ways to overcome the new situation together with their partner. The overall theme was 'A balance between emotional and physical closeness' emerged from 30 codes that were condensed into five subcategories and two categories: 'A sensual relationship' and 'A sexual relationship'. The first category constituted the subcategories 'Feeling of intimacy' and 'The importance of the relationship'. The category 'A sexual relationship' was revealed from the subcategories 'Reluctance to engage in sexual activity' and 'Partner inability to engage in sexual activity', and 'Acting for sexual rehabilitation'. Conclusions: The uncertainty that the women felt about their anatomical changes after radical cystectomy created a sexual anxiety and reluctance to resume intercourse. Even though the surgery had a major impact on their sexual life, the women tried to be sexually active. However, the meaning of sexual life was not just having sexual activity but also included closeness, affirmation, affection, and feeling attractive. Sexual counseling at an appropriate timepoint is essential to assure a balance between emotional and physical closeness, i.e. to regain sexual health.